Springback comparison between DP600 and DP800 steel grades - Almeida, Christyane Oliveira Leao [UNESP]; Lima, Luís Henrique Lopes; Dos Santos Pereira, Marcelo [UNESP] (IOP Publishing, 2020)
A comparative study of the springback effect, otherwise known as elastic return, on Dual Phase DP600 and DP800 steel sheets is reported herein, which have been widely used in the automotive industry due to having good mechanical properties, such as high strength and ductility if compared to conventional steels. For such a purpose, it is proposed to analyze whether anisotropy and varying forming parameters interfere with the springback effect or not. The parameters selected to compare DP600 with DP800 dual phase steels were descending speed of 4 mm min-1 along the vertical axis of sheets until reaching internal bending angle of 30 degrees during bending tests at two rolling angles (0 and 90 degrees), thus forming a U-shaped steel sheet. In addition to bending tests, tensile tensting and Vickers microhardness tests have been performed at three rolling angles (0, 45 and 90 degrees). It was concluded that punching rate, internal bending angle, observation time and rolling angle exert an influence on the springback effect. Thereby, there is an important contribution to areas that require quality in formability, such as vehicle structure, which must have high impact strength and energy absorption. Steel sheets with increasingly smaller thicknesses are able to reduce density, product cost and greenhouse gases emissions from automobiles.
Keywords: DP 600; DP 800; high strength steel; springback